2020
DOI: 10.3390/nu12041197
|View full text |Cite
|
Sign up to set email alerts
|

Better Dietary Knowledge and Socioeconomic Status (SES), Better Body Mass Index? Evidence from China—An Unconditional Quantile Regression Approach

Abstract: Obesity is a rapidly growing public health threat in China. Improvement of dietary knowledge may potentially reduce the risk of obesity and being overweight. However, existing studies focus on measuring the mean effects of nutrition knowledge on body mass index (BMI). There is a lack of literature on the effect of dietary knowledge on BMI, and the potential heterogeneity of the effect across the whole BMI distribution and across socioeconomic status (SES) groups. This study aims to investigate the heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Some controversial results were also reported regarding the associated factors of the dietary knowledge level. For example, Zhou et al [24] and Yu et al [25] found that the dietary knowledge of adults had no significant influence on overweight and obesity, possibly due to a lack of systematic dietary knowledge and inadequate guidance on overweight and obesity. While Laz et al [26] suggested that an increase in nutrition knowledge may promote healthy weight control behaviors among low-income reproductive-age women.…”
Section: Introductionmentioning
confidence: 99%
“…Some controversial results were also reported regarding the associated factors of the dietary knowledge level. For example, Zhou et al [24] and Yu et al [25] found that the dietary knowledge of adults had no significant influence on overweight and obesity, possibly due to a lack of systematic dietary knowledge and inadequate guidance on overweight and obesity. While Laz et al [26] suggested that an increase in nutrition knowledge may promote healthy weight control behaviors among low-income reproductive-age women.…”
Section: Introductionmentioning
confidence: 99%
“…Findings on the impact of dietary knowledge on health differ among different studies, which may be due to ignoring the heterogeneity of the samples [ 23 , 28 , 29 ]. Our heterogeneity analyses suggest that the impacts of dietary knowledge on health are stronger for individuals with a lower level of education and for rural residents.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars argue that more knowledge of diet usually leads to better health [ 11 , 26 ]. However, there are also studies suggesting that dietary knowledge is not translated into healthier food choices [ 27 ], and so has no positive impacts on health [ 28 , 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is known that factors like too high energy supply, too little physical activity, a diet rich in simple sugars and saturated fatty acids increase the risk of overweight and obesity in children [13]. The results of some studies indicate that nutritional awareness is not signi cantly related to BMI, which means that the knowledge of the principles of proper nutrition is not su cient in the effective prevention of overweight and obesity [14,15]. The very knowledge of nutrition does not limit the scale of the phenomenon.…”
Section: Purposementioning
confidence: 99%